2009
DOI: 10.1016/j.tig.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of transposable elements: towards a community ecology of the genome

Abstract: Like ecological communities, which vary in species composition, eukaryote genomes differ in the amount and diversity of transposable elements (TEs) that they harbor. Because TEs have a considerable impact on the biology of their host species, we need to better understand whether their dynamics reflects some form of organization or is primarily driven by stochastic processes. Here we borrow ecological concepts on species diversity to explore how interactions between TEs can contribute to structure TE communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
151
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 79 publications
6
151
0
Order By: Relevance
“…It has been recently suggested that the relationships between genome components (including genes, transposable elements, or any sequence able to persist over evolutionary time) were similar to the relationships between individuals or species in ecosystems (10,49,50), although the possibility to apply ecological formalism to genome evolution remains questionable (51). Here, we brought substantial evidence that the relationships between autonomous and nonautonomous mariner TE copies were analogous to parasitism: Mos1 copies (the "hosts") are able to survive and replicate by themselves, whereas peach copies (the "parasites") are unable to transpose without Mos1 copies.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently suggested that the relationships between genome components (including genes, transposable elements, or any sequence able to persist over evolutionary time) were similar to the relationships between individuals or species in ecosystems (10,49,50), although the possibility to apply ecological formalism to genome evolution remains questionable (51). Here, we brought substantial evidence that the relationships between autonomous and nonautonomous mariner TE copies were analogous to parasitism: Mos1 copies (the "hosts") are able to survive and replicate by themselves, whereas peach copies (the "parasites") are unable to transpose without Mos1 copies.…”
Section: Resultsmentioning
confidence: 99%
“…TEs must therefore be considered to be integrated components of the genomes, which have played a major role in evolution. It is proposed that it might be more accurate to view the genome as an ecological ecosystem in which the TE families and subfamilies correspond to the ''species'' of an ecosystem (Brookfield 2005;Mauricio 2005;Le Rouzic et al 2007;Venner et al 2009). These ideas suggest that the term ''controlling element,'' initially proposed by B. McClintock, was appropriate, even if all TE insertions do not have this ''gene-controlling'' capacity.…”
Section: Transposable Elements As Players In Evolutionmentioning
confidence: 99%
“…For example, workers have attempted to explain the proliferation of individual TE lineages and why the genomes of more complex organisms tend to contain more TEs than do simpler ones (11,12). We take an approach common in community ecology and ask what controls the relative abundance of different TE lineages.…”
mentioning
confidence: 99%